Diffuse Scattering Directive Model Parameterization Method for Construction Materials at mmWave Frequencies - Ming-Hao Ren; Xi Liao; Jihua Zhou; Yang Wang; Yu Shao; Shasha Liao; Jie Zhang (International Journal of Antennas and Propagation)
The determination for diffuse scattering model parameters is of critical importance to improve the accuracy of prediction and analysis for millimeter-wave radio propagation. In this paper, a reliable parameterization method with a simplified tuning procedure for a diffuse scattering model is proposed and validated based on measurements and ray-tracing simulations. Typical construction materials are measured from 40 GHz to 50 GHz, and the complex permittivity is estimated by the propagation coefficients match method. The directive model, which can better characterize the scattering patterns of construction materials in this paper, is adopted to calibrate the ray-tracing simulation. Model parameterization is performed and simulated results with the optimal model parameters show distinct accuracy improvement.